LEUKOCYTE REDUCTION FILTERS AND INFUSION DEVICE FOR RED BLOOD CELL TRANSFUSION - Morino, Sakiko; Takagi, Shojiro; Buseki, Yuuji; Henmi, Junko; Fujino, Shinji (Journal of the Japan Society of Blood Transfusion, 2003)
we studied the influence on blood cells when red blood cells were filtered with leukocyte reduction filters under the midpress-type infusion pump. At regular (5ml/min) and high (20ml/min) flow rates of infusion, red blood cells were filtered with a small delay. Filtered blood cells showed less damaged with regard to red cell morphology. A negligible increase in supernatant hemoglobin concentration was detected in filtered blood products, but no significant increase in supernatant potassium concentration was observed. The number of residual white blood cells after filtration was significantly reduced even at the forced high flow rate of infusion. Our results show that leukocyte reduction filters (Purecell RC and Imugard III-RC) are safely applicable to the midpress-type infusion pump for red blood cell transfusion.